2018
DOI: 10.1111/apt.14665
|View full text |Cite
|
Sign up to set email alerts
|

High body mass index is associated with increased risk of treatment failure and surgery in biologic‐treated patients with ulcerative colitis

Abstract: BMI is independently associated with increased risk of treatment failure in biologic-treated patients with UC, independent of dosing regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 30 publications
3
52
0
Order By: Relevance
“…One randomized controlled trial showed that weight reduction in patients yielded improved Psoriasis Area and Severity Index scores . Moreover, a retrospective cohort study demonstrated that obesity was independently associated with biologic treatment failure in biologic‐treated patients with ulcerative colitis . The results of the current study, in consideration with the previous studies, underscore the importance of managing weight in patients with psoriasis to improve treatment persistence and therefore therapeutic outcome.…”
Section: Discussionsupporting
confidence: 65%
“…One randomized controlled trial showed that weight reduction in patients yielded improved Psoriasis Area and Severity Index scores . Moreover, a retrospective cohort study demonstrated that obesity was independently associated with biologic treatment failure in biologic‐treated patients with ulcerative colitis . The results of the current study, in consideration with the previous studies, underscore the importance of managing weight in patients with psoriasis to improve treatment persistence and therefore therapeutic outcome.…”
Section: Discussionsupporting
confidence: 65%
“…This contrasts with recent findings showing that higher body mass index (BMI) is associated with an increased risk of treatment failure and surgery in biologic-treated patients with UC, however, this was observed mostly for patients who were overweight (BMI, !25 kg/m 2 ) or obese (BMI, !30 kg/m 2 ). 23 Unfortunately, BMI was not available as a size measure in the current data set to evaluate similar cut-off values for obesity. Variables associated with endoscopic healing at week 30 were as follows: no use of corticosteroids at baseline, female sex, and higher week 30 IFX concentration.…”
Section: Discussionmentioning
confidence: 99%
“… 17 , 25 , 26 Obesity is associated with persistent disease activity, has been shown to negatively impact biologic therapy and surgical outcomes, and is associated with poorer mental health (anxiety and depression). 27 , 28 Routine nutrition screening will also assist in early identification of unhealthy weight gain and patients requiring individualized counseling to prevent unwanted weight increases ( Figure 1 ). 10 …”
Section: Ibd Dietary Recommendations During Sars-cov2 Pandemic: Optimmentioning
confidence: 99%